FUNCTIONS OF THE HIGHER MILITARY EDUCATIONAL INSTITUTION CADET AS SUBJECT OF SELF-MANAGING INDEPENDENT STUDY - Kucheriavyi, A. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
Cadet’s self-directed independent study is an inherent part of learning process. Its significance is increasing in conditions of permanent enlargement of learning content, Army Forces’ acquirement of new war experience, technological modernization of army etc. Therefore cadets’ selfdirected independent study requires search of new ways of increasing its efficiency. Certain opportunities regarding this issue may be carried out by improvement of managing it. The classic system of higher educational institution management includes officials of different levels; however, a cadet does not belong to them. At the same time, a future officer manages self-directed independent study. This circumstance is not sufficiently studied by military pedagogy researchers and determines a research problem. Its solving requires investigation of a future officer’s functions which he or she performs in the process of self-managing independent learning work. Accordingly, the paper’s goal is studying these functions. On the basis of scientific works in the field of classic and educational management and also our own experience we have defined five functions, several of them have derivatives. The cadet’s motivational function has system motivational and self-motivational derivatives. First of them is determined by cadet’s impact on the whole system of educational institution management. The second derivative consists of defining by a cadet his needs for learning, personal and professional development and their implementation in the process of self-directed independent study. The constructive function also has several derivatives. Among of them the function of target self-determination is orienting a cadet to determining the learning goals, studying particular courses, independent learning out of the lesson schedule, doing various assignments. And the function of creating learning conditions requires solving any issues regarding onward executing of self-directed independent study. The organizational function consists of such derivatives as planning independent work out of the lesson schedule and its current self-organizing. The functions of self-stimulating and selfcontrol are also inherent parts of the complex of cadet’s managing functions. Thus, all the functions create a certain system which characterizes a cadet as a self-manager of self-directed independent study.
Keywords: cadet, self-directed independent study, functions, management, higher military educational institution